THE RELATIONSHIPS AMONG STERNBERG'S TRIARCHIC ABILITIES, GARDNER'S MULTIPLE INTELLIGENCES, AND ACADEMIC ACHIEVEMENT - (:unkn) unknown (SOC PERSONALITY RES INC, 2014)
In this study I investigated the relationships among Sternberg's Triarchic Abilities (STA), Gardner's multiple intelligences, and the academic achievement of children attending primary schools in Istanbul, Turkey. Participants were 172 children (93 boys and 81 girls) aged between 11 and 12 years. STA Test (STAT) total scores were significantly and positively related to linguistic, logical-mathematical, and intrapersonal test scores. Analytical ability scores were significantly positively related to only logical-mathematical test scores, practical ability scores were only related to intrapersonal test scores, and the STAT subsections were significantly related to each other. After removing the effect of multiple intelligences, the partial correlations between mathematics, social science, and foreign language course grades and creative, practical, analytical, and total STAT scores, were found to be significant for creative scores and total STAT scores, but nonsignificant for practical scores and analytical STAT scores.
Keywords: Sternberg's Triarchic Abilities Test; multiple intelligences; academic achievement; children; intelligence; CONSTRUCT-VALIDATION